MOTIF HIAS PADA PELIPIT CANDI - Rita Istari (BRIN, 2013)
Decorative motifs found in Hindu and Buddhist temples, usually are depicted on almost all parts of buildings. Decorative motif in the form of reliefs consisted of geometric ornaments, nature, plants, animals, and humans. Relief there is a series of panels connected to one another with stories taken shadow-play epic. Fables are also often depicted. Stories with animals as the main character containing morale for human’s life. Temple has 3 main parts, namely the base, body, and roof of the temple. In addition there is also a section called cornice and plinth. This serves as a separator between the three parts of the temple. To add beauty and give the impression of a slender building, then on cornice and plinth was carved decorative motif that surrounds the temple. The various decorative motifs will be discussed at length in this paper.